2022
DOI: 10.1111/joms.12848
|View full text |Cite
|
Sign up to set email alerts
|

‘We're all Born Naked and the Rest is Drag’: Spectacularization of Core Stigma in RuPaul's Drag Race

Abstract: How can organizations capitalize on core stigma through spectacles? In this paper, we adopt a performativity perspective to address this question. Specifically, we analyze how an assemblage of different actors within and around an organization contributes to the spectacularization of stigma and thus brings a new reality into being. In this new reality, rather than stigma being concealed, it is normalized, and the organization capitalizes on it to enhance success. We focus on RuPaul's Drag Race as a stigmatized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
0
14
0
1
Order By: Relevance
“…We hope this special issue and this editorial can help consolidate existing research on organizational stigma, and open new areas for contribution, both conceptually and empirically. From more traditional contexts – international business operations (Tsui‐Auch et al, 2022) or banking (Frandsen and Morsing, 2022; Roulet, 2015) to less traditional ones – television reality shows on drag queens (Campana et al, 2022), martial arts (Helms and Patterson, 2014) or kink associations (Coslor et al, 2020) – studies of organizational stigma have shown the polyvalence and theoretical usefulness of the concept. While the literature is still evolving, it is beginning to reach a maturation phase, with stabilized definitions and links with other relevant areas of research and connate concepts (Pollock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We hope this special issue and this editorial can help consolidate existing research on organizational stigma, and open new areas for contribution, both conceptually and empirically. From more traditional contexts – international business operations (Tsui‐Auch et al, 2022) or banking (Frandsen and Morsing, 2022; Roulet, 2015) to less traditional ones – television reality shows on drag queens (Campana et al, 2022), martial arts (Helms and Patterson, 2014) or kink associations (Coslor et al, 2020) – studies of organizational stigma have shown the polyvalence and theoretical usefulness of the concept. While the literature is still evolving, it is beginning to reach a maturation phase, with stabilized definitions and links with other relevant areas of research and connate concepts (Pollock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in this special issue very much flesh out those links between internal and external audiences (Campana et al, 2022; Frandsen and Morsing, 2022; Tsui‐Auch et al, 2022) in all their multiplicity and complexity. Their approach relies on an effort to delimit audiences and unpack the situational drivers of their reactions to explain the outcomes of organizational stigma.…”
Section: The Future Of Organizational Stigma Studiesmentioning
confidence: 99%
See 3 more Smart Citations